Experimental Study on the Flexural Behavior of Connected Precast Concrete Square Piles - Zhongji Dong; Faning Dang; Jun Gao (Advances in Civil Engineering)
Part of deep foundation pit support engineering needs to select connected precast concrete square piles (CPCSPs). Under the premise that the quality of precast concrete square piles (PCSPs) meets engineering requirements, the quality of CPCSPs becomes the key factor to ensure the safety of foundation pit support structures. This paper puts forward a new connection technology of CPCSPs and carries out the flexural behavior experiment of unconnected precast concrete square piles (UPCSPs) and CPCSPs. The distribution of crack and strain on different surfaces of UPCSPs and CPCSPs are measured by carbon fiber composite strain sense optical cables, glass fiber composite strain sense optical cables, and fixed-point polyurethane strain sense optical cables. The anti-crack load, ultimate load, bending moment, and flexural deformation of UPCSPs and CPCSPs are measured. The experimental results of UPCSPs and CPCSPs are compared. The results show that the anti-crack strength of CPCSPs is greatly increased while the flexural deformation of CPCSPs is decreased before the occurrence of crack. With the development of crack (failure stage), the outside areas of hoop steel plate exhibit cracks. At this moment, the strength of CPCSPs is no longer controlled by the strength of middle areas. The ultimate strength of CPCSPs is basically equivalent to that of UPCSPs. The ultimate bending moment of CPCSPs is higher than its design value (about 66%∼76%). The selection of CPCSPs in the design of foundation pit support has good reliability.